FERROSEN KALKON YAN GRUPLU SİKLOTRİFOSFAZEN BİLEŞİĞİNİN FOTOFİZİKSEL VE ELEKTRİKSEL ÖZELLİKLERİNİN ARAŞTIRILMASI - KATTAN, M-MAHDI (Fırat Üniveristesi, 2024)
Bu tez çalışmasında azit uç gruplu kalkon bileşiklerinin kolay bir şekilde ve yüksek verimlerde siklotrifosfazen halkasına bağlanmasını sağlamak için ?Klik Kimyası? reaksiyonlarından yararlanılmıştır. Azit uç gruplu asetofenon bileşiğinden yola çıkarak ferrosenkarboksaldehit ile NaOH varlığında etanol içerisinde etkileştirilerek yeni azit uç gruplu ferrosen-kalkon bileşiği (4-N3-Ferrosen-Kalkon) sentezlendi. Elde edilen bu kalkon bileşiğinin (4-N3-Ferrosen-Kalkon) alkin uç gruplu dispirofosfazen bileşiği (DPP-PA) ile klik yöntemi kullanılarak etkileştirilmesi sonucu yeni siklotrifosfazen bileşiği (DFF-PA-Klik-Ferrosen-Kalkon) ilk kez bu çalışma kapsamında sentezlendi. Sentezlenen bileşiklerin yapısal karakterizasyonları FT-IR, 31P, 1H, 13C-APT NMR ve MALDI-TOF MS kütle spektroskopisi yöntemleri ile aydınlatıldı. Ayrıca bileşiklerin termal özellikleri DSC ve TGA yöntemleri kullanılarak belirlendi. Sentezlenen spirofosfazen bileşiğinin dielektrik özellikleri ve yarıiletken davranışlarını belirleyebilmek için dielektrik sabiti, dielektrik kayıp faktörü ve AC ve DC iletkenlik ölçümleri yapıldı. Yarıiletken özellik taşıyan 4-N3-Ferrosen-Kalkon ve DFF-PA-Klik-Ferrosen-Kalkon bileşiği ile yeni tip diyotlar hazırlandı. Hazırlanan diyotların doğrultma özellikleri ve ışığa karşı fotodiyot özellikleri incelendi. Fotodiyot özellikleri farklı ışık şiddetine (20 mW/cm2-100 mW/cm2) sahip güneş ışığı altında araştırılarak diyotun ara yüzey kapasitansı, direnci ve iletkenlikleri farklı voltaj aralıklarında incelenerek belirlendi. Elde edilen veriler incelendiğinde bileşiklerin ışığa karşı duyarlılık taşıdığı ve fotodiyot özellik gösterdiği tespit edildi. Sonuç olarak üretilen diyotların fotoiletken davranış sergilediğini ve optoelektronik cihazlarda diyot ve fotodiyot malzeme olarak kullanılabilme potansiyeline sahip olduğunu göstermiştir.

In this thesis study, "Click Chemistry" reactions were used to ensure the binding of chalcone compounds with azide end groups to the cyclotriphosphazene ring easily and in high yields. Starting from the acetophenone compound with azide end group, a new ferrocene-chalcone compound with azide end group (4-N3-Ferrocene-Chalcone) was synthesized by interacting it with ferrocenecarboxaldehyde in ethanol in the presence of NaOH. At the bottom of the abstract, there should be keywords that describe the topic. A minimum of 3 (three) and a maximum of 6 (six) keywords are used. As a result of the interaction of this obtained chalcone compound (4-N3-Ferrocene-Chalcone) with the dispirophosphazene compound with alkyne end group (DPP-PA) using the click method, the new cyclotriphosphazene compound (DFF-PA-Click-Ferrocene-Chalcone) was synthesized for the first time within the scope of this study. Structural characterizations of the synthesized compounds were elucidated by FT-IR, 31P, 1H, 13C-APT NMR and MALDI-TOF MS mass spectroscopy methods. Additionally, the thermal properties of the compounds were determined using DSC and TGA methods. Dielectric constant, dielectric loss factor and AC and DC conductivity measurements were made to determine the dielectric properties and semiconductor behavior of the synthesized spirophosphazen compound. New types of diodes were prepared with 4-N3-Ferrocene-Chalcone and DFF-PA-Click-Ferrocene-Chalcone compounds, which have semiconductor properties. The rectification properties of the prepared diodes and photodiode properties against light were examined. Photodiode properties were investigated under sunlight with different light intensities (20 mW/cm2-100 mW/cm2) and the interface capacitance, resistance and conductance of the diode were determined by examining them at different voltage ranges. When the data obtained was examined, it was determined that the compounds were sensitive to light and showed photodiode properties. As a result, it has been shown that the produced diodes exhibit photoconductive behavior and have the potential to be used as diodes and photodiode materials in optoelectronic devices.
Investigation of synthesis, photophysical and electrical properties of cyclotriphosphazene compound with ferrocene chalcone side group by click method
Keywords: Kimya